Fatal accidents at work in agriculture associated with alcohol intoxication in Lower Silesia in Poland - Tomasz Jurek; Marta Rorat (Nofer Institute of Occupational Medicine, 2017)
Background: Determining the prevalence of alcohol intoxication and the level of intoxication in victims of fatal occupational accidents is necessary to improve work safety. The circumstances of the accident and the time between alcohol consumption and death are important factors. Material and Methods: A retrospective review of 18 935 medico-legal autopsy reports and toxicological reports performed in the Department of Forensic Medicine at the Wroclaw Medical University, Poland, in the years 1991-2014. The study protocol included circumstances, time and cause of death, injuries, quantitative testing for the presence of ethyl alcohol, gender and age. Results: There were 98 farm-related fatalities. There were 41.8% (N = 41) of victims who had been intoxicated - 95.1% (N = 39) of them were males aged 19-70 years old, 4,9% (N = 2) were females aged 37-65 years old. In 8 cases the blood alcohol concentration (BAC) was 50-150 mg/dl; in 15 cases it was 150-250 mg/dl and in 18 cases it was > 250 mg/dl. In 21 cases, the BAC was determined using alternative material and 76% (N = 16) victims were in the alcohol elimination phase with 19% (N = 4) victims in the alcohol absorption phase. The most common causes of death were traffic accidents, drowning and deaths resulting from being caught in or hit by moving parts of machinery or equipment. Conclusions: Alcohol consumption is a crucial risk factor in fatal agricultural accidents. In order to establish the time of alcohol consumption, all victims of agricultural accidents should be tested for alcohol concentration in their blood and urine or vitreous. Improving safety at work requires that the sobriety of employees should be monitored before and during work. Med Pr 2017;68(1):23-30